FRI0224 A New Method to Assess Activity Limitations in Patients with Hip and Knee Osteoarthritis: the Animated Activity Questionnaire (AAQ): Part 1. Development, Validity and Reliability. (10th June 2014) - Peter, W.F.; Loos, M.; de Vet, R.C.; Boers, M.; Harlaar, J.; Roorda, L.D.; Poolman, R.W.; Scholtes, V.A.; Boogaard, J.; Buitelaar, H.; Steultjens, M.; Roos, E.M.; et al.
Abstract : Background: Self-report questionnaires and performance-based tests correlate moderately in measuring activity limitations, indicating that they measure different aspects. Self-reports measure mainly the patients' perception which may lead to cross-cultural differences. Performance-based tests measure an artificial situation, is resource-intensive and burdensome for patients. To overcome these drawbacks we developed and tested a pilot version of an animated activity questionnaire (AAQ), which demonstrated some promising features[1]. Objectives: Development of the computerized Animated Activity Questionnaire (AAQ) to assess activity limitations in patients with hip/knee osteoarthritis (OA), and study validity and reliability. Methods: Based on the ICF core set for OA, focus groups of patients, and existing measurement instruments, the AAQ was developed. In 102 patients correlations were calculated between AAQ and self-reported Hip disability and Knee injury Osteoarthritis Outcome ADL Score (H/KOOS). In addition internal consistency was calculated. In a subgroup of 38/102 patients also correlations with performance based tests (Stair Climbing Test (TCT), Timed Up and Go test (TUG) and the 30 second Chair Stand Test (CST)) were calculated. Test-retest reliability was assessed by repeated scoring in a subgroup of 28/102 patients. Results: The AAQ includes animated videos of 17 basic daily activities with 4 levels of increasing difficulty (check the following link for two examples: http://kmin-vumc.nl/_14_0.html ). Patients were asked to select the video that best matched their own performance. Cronbach's alpha was 0.95. In 102 patients correlation with H/KOOS ADL scores was high (0.83). In the subgroup of 38/102 patients the AAQ correlated highly with the TCT, TUG and CST (0.67, 0.61, and 0.71, respectively) and the H/KOOS (0.79). For test-retest reliability in 28/102 patients a Intraclass Correlation Coefficient of 0.97 (95% CI 0.93-0.99) was found. Conclusions: The AAQ has a high internal consistency and excellent test-retest reliability. The validity is supported by high correlations with performance-based tests, and the correlation with the self-reported H/KOOS was even higher than expected. Since the AAQ needs no reading ability or translation, it has potential for international use. Continuing research will focus on construct validity and cross-cultural validity. References: Terwee CB et al. Development and Validation of the Computer-Administered Animated Activity Questionnaire to Measure Physical Functioning of Patients With Hip or Knee Osteoarthritis. Phys Ther. 2013, Sep 12 [Epub ahead of print]. Acknowledgements: Funded by EULAR Patient Reported Outcome research grant. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3220